Domestic Tension: Representation of Muslim artist's body in online performance. (1st December 2021) - Hejazi, Seyed Jafar
This article investigates the relevance between body representation in online performance and Islamic art by studying Domestic Tension, an online performance by Iraqi-born artist Wafaa Bilal. Bilal lives under online participant shoots, with a paintball gun, in a gallery and broadcasts the event 24/7 on the internet. Islam and its laws, related to the body, played a central role in this performance and remained out of sight. The Qur'an mentioned the body rarely in verses; therefore, the Hadith is the most trustworthy reference to learn. Based on Hadith, figural representation between Muslims is banned, and the makers of these pictures get punished in the other world. This prohibition must be the main reason for Muslim artists' use of symbols and signs to represent figures. In the virtual space artworks, the artist kills his own body to represent the body as a basic image, codes and sings. By analysing Domestic Tension, I argue that the connection between Muslim artists' perception of the body and the definition of semiotics body in online performance can be a reason for artists with an Islamic background to use the internet as a medium to express themselves.